Poisoning Cases Admitted to the Pediatric Emergency Department: A Retrospective Evaluation - Yusuf Güzel; Fatih Battal; Hakan Aylanç (Galenos Yayinevi, 2022)
Introduction:Intoxication in childhood is an important preventable public health problem and can cause morbidity and mortality. In this study, we investigated the clinical and demographic characteristics of patients who presented to our pediatric emergency department in the last 4 years due to poisoning.Methods:Records of 238 children aged 1 month to 18 years who applied to Çanakkale Onsekiz Mart University Faculty of Medicine, Pediatric Emergency Department between January 2015 and January 2019 were evaluated retrospectively. Cases were examined in terms of age, gender, time to first medical intervention after drug intake, cause of poisoning, intake method, and symptoms.Results:Of the 238 patients, 45% were female. The median age was 59.34 (interquartile range: 3-215) months, and 57.15% of the patients were <5 years old, 23.1% were >12 years old, and 8.1% were accidental cases, 26.9% were poisoned following a suicide attempt. The mean time to presentation to our center was 91.2±75.6 min. Poisoning most commonly occurred in the spring months (29.83%). Among drug poisons, analgesics were the most common (23.41%); 60.51% of the cases were asymptomatic, while the most common symptoms were nausea and vomiting.Conclusion:Suicidal poisoning is seen less frequently in children. The main cause of poisoning is an accidental intake of medication. In addition to the measures taken by caregivers, parents, drug manufacturers, and healthcare workers, determining the epidemiological and clinical characteristics of poisoning will contribute to the reduction of mortality and morbidity among children.